2019
DOI: 10.1002/er.4304
|View full text |Cite
|
Sign up to set email alerts
|

Performance investigation of salt gradient cylindrical solar pond integrated and nonintegrated with evacuated tube solar collectors

Abstract: Summary In this study, the energetic and exergetic efficiencies of a salt gradient cylindrical solar pond (SGCSP) that integrated and nonintegrated evacuated tube solar collectors (ETSCs) are investigated to improve daily heat preservation performance of the heat storage zone (HSZ). The integrated system is consisted of an SGCSP and four ETSCs. The SGCSP has a surface area of 2 m2, a depth of 1.65 m, salty water layers at different densities, and HSZ in which the cylindrical serpentine type heat exchanger (CSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The performance of the SPs was calculated and compared. Atiz et al 18 investigated the effect of using evacuated tube solar collectors as a supplemental heat source on the thermal performance of SP. The energetic and exergetic performances were calculated which is dependent on the number of collectors by using experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the SPs was calculated and compared. Atiz et al 18 investigated the effect of using evacuated tube solar collectors as a supplemental heat source on the thermal performance of SP. The energetic and exergetic performances were calculated which is dependent on the number of collectors by using experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, using solar pond extracted heat for ejector refrigeration cycle coupled with a thermoelectric generator, cooling production was carried out, showing that under optimum conditions, the energy and exergy efficiencies were about 28.26% and 29.95%, respectively [36]. Atiz et al [7] investigated the energy and exergy of a cylindrical solar pond that integrated and nonintegrated with solar collectors. They showed that the highest and lowest energy and exergy efficiencies belonged to the solar pond with four collectors and without collector, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum operating temperature of the solar pond with the addition of external heat is ranged (from 70 C to 80 C). Also, Atiz et al 28 studied the variables that affect the thermal performance of a solar pond using solar collectors. Bozkurt and Karakilcik 29,30 presented a thermal analysis of the energy productivity of a solar pond combined with collectors.…”
mentioning
confidence: 99%